Researching police reform: experiences from Scotland and the Netherlands - Fyfe, Nicholas R. (Introduction to policing research, 2024)
In recent years Scotland and the Netherlands have both experienced fundamental transformations in the structure, organization and governance of their police systems and these changes have attracted significant research attention. Drawing on their own close involvement with the reform processes in these countries, the authors focus on how research played a key role in preparations for reform, in examining the initial impacts and implications of the changes, and in evaluating the medium and longer term strategic outcomes of reform. The chapter concludes with a critical assessment of what difference research on police reform can make in terms of informing future policy preferences for changes to police systems and structures.